Pandora's toolbox : the hopes and hazards of climate intervention - Smith, Wake (Cambridge : Cambridge University Press, 2022)
Reaching net zero emissions will not be the end of the climate struggle, but only the end of the beginning. For centuries thereafter, temperatures will remain elevated; climate damages will continue to accrue and sea levels will continue to rise. Even the urgent and utterly essential task of reaching net zero cannot be achieved rapidly by emissions reductions alone. To hasten net zero and minimize climate damages thereafter, we will also need massive carbon removal and storage. We may even need to reduce incoming solar radiation in order to lower unacceptably high temperatures. Such unproven and potentially risky climate interventions raise mind-blowing questions of governance and ethics. Pandora's Toolbox offers readers an accessible and authoritative introduction to both the hopes and hazards of some of humanity's most controversial technologies, which may nevertheless provide the key to saving our world.
Title from publisher's bibliographic system (viewed on 25 Feb 2022).
Keywords: Carbon dioxide mitigation -- Technological innovations; Global warming -- Prevention -- Technological innovations